The School Health Programs Status in Basic Schools as Viewed by Teachers in Governmental and UNRWA Schools in Nablus District - Dalia Rahmi Abd-Alfattah Toukan (My University, 2003)
he current study aimed to investigate the status of school health programs in Governmental and UNRWA basic schools in Nablus District.The study problem concentrated mainly on answering the following question: What is the reality of school heath programs in governmental and UNRWA basic schools in Nablus district? To answer this question, the following sub- questions were formulated: What is the effect of the (sex, scientific degree, experience, sponsoring party, site of school, school sessions) variables on perception of basic school teachers concerning school health programs in Nablus district? From the previous questions, hypothesis of study were formulated: There is no significant mean differences at level (α = 0.05) on perception of basic school teachers toward school health programs regarding (sex, scientific degree, experience years, sponsoring party, site of school, school sessions) variables.To answer the previous questions and, to test hypothesis the researcher studied a randomized sample composed of (443) of basic school teachers, and the sample was about (36%) of the total population which was (1173) teachers. The tool of study was a questionnaire which was developed by the researcher by using the different literature of views, and studies made on same subject , the questionnaire was composed of (72) paragraphs divided to (4) aspects (Environmental health, physical health, psychological health, and social health). The questionnaire was investigated for reliability which was (0.90), validity, and internal compatibility by using (Cronbach-Alpha).The collected data were treated by using the computerized statistical program (SPSS) by using the following methods to analyze the result: 1.Frequencies, arithmetical means, percentages, and standard deviations. 2.Independent “t” test. 3.One Way ANOVA test. 4.Scheffe test.The results of study were as follows: ▪The four aspects of study had the following percentages: Environmental health aspect (68%), physical health aspect (66%) , psychological health aspect (69%), social health aspect (76%) and total degree of school health program status (70%). ▪There is no significance to the following variables (Sex, scientific degree, experience years, school sessions) on the status of school health programs in its four aspects (Environmental, physical, psychological , and social health ) in governmental, and UNRWA basic schools in Nablus district. ▪There insignificance of (sponsoring party) variable on the status of school health programs in its four fields, particularly in environmental health aspect in favor to governmental schools. ▪There is coefficient significance to site of school variable in favor to those located in the city.Recommendations: The researcher recommends the following: ▪Improving the environmental health in schools sponsored by (UNRWA). ▪Improving the school health programs in villages. ▪ Reconstructing schools that were destroyed by Israeli aggression so as to prevent any negative effects on school health programs. ▪Conducting other studies on school health programs in other districts.

هدفت هذه الدراسة للتعرف إلى واقع برامج الصحة المدرسية للمراحل الأساسية الدنيا في المدارس الحكومية، والمدارس التابعة لوكالة الغوث من وجهة نظر معلمي ومعلمات هذه المراحل في محافظة نابلس . وقد تحددت مشكلة الدراسة في الإجابة عن السؤال الآتي وهو:- ما واقع برامج الصحة المدرسية للمراحل الأساسية الدنيا في المدارس الحكومية والتابعة لوكالة الغوث من وجهة نظر المعلمين والمعلمات في محافظة نابلس ؟. وللإجابة عن هذا السؤال تم اشتقاق عدد من الأسئلة الفرعية، والتي تم دمجها في سؤال واحد وهو: - ما تأثير متغير الجنس، والمؤهل العلمي، وسنوات الخبرة، والجهة المشرفة على المدرسة، وموقع المدرسة، ودوام المدرسة في وجهة نظر معلمي ومعلمات المراحل الأساسية الدنيا في المدارس الحكومية والمدارس التابعة لوكالة الغوث في محافظة نابلس؟. وقد انبثقت عن الاسئلة السابقة الفرضيات الآتية، والتي تم دمجها في فرضية واحدة وهي: -لا توجد فروق ذات دلالة احصائية عند مستوى الدلالة ( α=0.05) من وجهة نظر معلمي ومعلمات المراحل الأساسية الدنيا نحو واقع برامج الصحة المدرسية بمجالاتها في المدارس الحكومية والمدارس التابعة لوكالة الغوث تعزى لمتغير الجنس، والمؤهل العلمي، وسنوات الخبرة، والجهة المشرفة على المدرسة، وموقع المدرسة، ودوام المدرسة. وللإجابة عن الأسئلة السابقة واختبار الفرضيات، قامت الباحثة بدراسة عينة عشوائية مكونة من (433) معلماً ومعلمة من المراحل الأساسية الدنيا، وبنسبة (36%) من المجتمع الأصلي المكون من (1173) معلماً ومعلمة، حيث تم توزيع الاستبانات على المدارس بعد الحصول على الأذونات الرسمية من مديرية التربية والتعليم، ومكتب وكالة الغوث في مدينة نابلس.وقد استخدمت الباحثة أداة للدراسة، وهي عبارة عن استبانة قامت الباحثة بتطويرها بالاستفادة من الأدب التربوي والدراسات السابقة عن الموضوع، وتكونت الاستبانة النهائية من (72) فقرة موزعة على (4) مجالات، وهي: (الصحة البيئية، والصحة الجسمية، والصحة النفسية، والصحة الاجتماعية ) وقد تأكدت الباحثة من صدقها من خلال عرضها على لجنة من المحكمين ، وتأكدت من ثباتها من خلال حساب معامل الاتساق الداخلي كرونباخ الفا، حيث وصل معامل الثبات الكلي (0.90). ولاختبار صحة الفرضيات السابقة، تمت معالجة البيانات إحصائيا باستخدام الرزمة الإحصائية للبحوث الاجتماعية (SPSS )، وذلك باستخدام المعالجات الآتية: - التكرارات والنسب المئوية والمتوسطات الحسابية والانحرافات المعيارية. - اختبار ( ت) لمجموعتين مستقلتين Independent T test. - تحليل التباين الأحاديِ ANOVA)(One Way. - اختبار شيفيه للفروق البعدية (Scheffe) لمعرفة لصالح من كانت الفروق بين المجموعات. وقد أسفرت الدراسة عن النتائج الآتية: - أن مجالات الدراسة حصلت على النسب الآتية : مجال الصحة البيئية (68%) ، والصحة الجسمية (66%)، والصحة النفسية (69%)، والصحة الاجتماعية(76%) والدرجة الكلية لواقع برامج الصحة المدرسية (70%). -لا توجد فروق دالة احصائيا في واقع برامج الصحة المدرسية بمجالاتها للمراحل الأساسية الدنيا في المدراس الحكومية، وكذلك التابعة لوكالة الغوث في محافظة نابلس تبعا لمتغيرات: الجنس، والمؤهل العلمي، وسنوات الخبرة، ودوام المدرسة. -توجد فروق دالة احصائيا في واقع برامج الصحة المدرسية بمجالاتها للمراحل الأساسية الدنيا في المدراس الحكومية، والمدارس التابعة لوكالة الغوث في محافظة نابلس تبعا لمتغيرات: الجهة المشرفة ولصالح المدارس الحكومية، وفي موقع المدرسة ولصالح المدارس التي تقع في المدينة. وقد أوصت الباحثة بالعمل على تحسين مجال الصحة البيئية في المدارس التي تشرف عليها وكالة الغوث، وإجراء المزيد من الدراسات حول موضوع برامج الصحة المدرسية وذلك في محافظات أخرى.
واقع برامج الصحة المدرسية للمراحل الأساسية الدنيا في المدارس الحكومية والمدارس التابعة لوكالة الغوث من وجهة نظر المعلمين والمعلمات في محافظة نابلس